Functional Oil Price Expectations Shocks and Inflation - Christina Anderl; Guglielmo Maria Caporale (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper investigates the inflation effects of oil price expectations shocks constructed as functional shocks, i.e. as shifts in the entire oil futures term structure (both standard and risk-adjusted). The latter are then included in a vector autoregressive model with exogenous variables (VARX) to examine the US case. Counterfactual analysis is also carried out to investigate second-round effects on inflation through the inflation expectations channel. These are found to be significant, in contrast to earlier studies based on standard oil price shocks. Additional nonlinear local projections including a shock decomposition exercise show that inflation and inflation expectations are primarily driven by changes in the curvature (level and slope) factor when the latter are anchored (unanchored). These findings provide useful information to policymakers concerning the impact of oil price expectations on inflation and inflation expectations.
Keywords: C32; E31; Q43; 330; functional shocks; oil price expectations; inflation anchoring; counterfactual analysis